2019
DOI: 10.1186/s42501-019-0036-4
|View full text |Cite
|
Sign up to set email alerts
|

Growth mechanisms and environmental implications of carbonate concretions from the ~ 1.4 Ga Xiamaling Formation, North China

Abstract: Carbonate concretions provide unique records of ancient biogeochemical processes in marine sediments, and have the potential to reflect seawater chemistry indirectly. In fine-siliciclastic settings, they preferentially form in organicrich mudstones, owing to a significant fraction of the bicarbonate required for carbonate precipitation resulted from the decomposition of organic matter in sediments. In the Member IV of the Xiamaling Formation (ca. 1.40-1. 35 Ga), North China, however, carbonate concretions occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 64 publications
(131 reference statements)
1
21
0
Order By: Relevance
“…It should be noted that although many scholars have analysed the influence of mineral composition on pore structure, most of the research results have not removed the concealment of TOC content on pore structure, and the correlation between each clay mineral composition and pore structure of different scales is rarely discussed under the removal of TOC concealment [ 23 , 29 , 46 ]. After removing the concealing effect of TOC content on the micro-nano pore structure, this study comprehensively and deeply reveals the influence of brittle minerals such as quartz and calcite, clay minerals such as smectite, I/S and illite, on the formation and development of the PV and SA of micropores, mesopores, and macropore.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that although many scholars have analysed the influence of mineral composition on pore structure, most of the research results have not removed the concealment of TOC content on pore structure, and the correlation between each clay mineral composition and pore structure of different scales is rarely discussed under the removal of TOC concealment [ 23 , 29 , 46 ]. After removing the concealing effect of TOC content on the micro-nano pore structure, this study comprehensively and deeply reveals the influence of brittle minerals such as quartz and calcite, clay minerals such as smectite, I/S and illite, on the formation and development of the PV and SA of micropores, mesopores, and macropore.…”
Section: Discussionmentioning
confidence: 99%
“…The thermal maturity reflects the dual effects of compaction and time experienced by shale. According to Liu et al [ 29 ], the Xiamaling shale in Zhangjiakou, Hebei has been in a slow subsidence and deep burying state for a long time since its deposition to the end of the Carboniferous; then, this shale started lifting at the beginning of the Permian and subsided rapidly in the middle of the Cretaceous. The negative relationship between EqRo and the TOC-normalized PV and SA of different nanoscale pores of the Ximaling shale is predominantly due to the deep progressive burial and compaction of the shale.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al 2012;Chen et al 2015b;Ye et al 2020). For example, MREE enrichments of the Mesoproterozoic Xiamaling carbonate concretions (Liu et al 2019) and the Ediacaran Doushantuo cap carbonates (Wu et al 2019) are both attributed to metal oxide reduction. Since carbonate samples generally have low TOC, it is reasonable to exclude organic matter as a candidate.…”
Section: B2 Mree Enrichmentmentioning
confidence: 99%
“…Some other studies, however, suggested a highly dynamic redox landscape for the mid‐Proterozoic ocean, with spatio‐temporally heterogeneous seawaters (e.g., Diamond & Lyons, 2018; Gilleaudeau & Kah, 2015; Hardisty et al., 2017; Planavsky et al., 2018; Poulton et al., 2010; Sperling et al., 2014; Tang et al., 2016). Multi‐proxy evidence from several sedimentary basins seems to support an episodic or spatially limited oxygenation model in the mid‐Proterozoic ocean that is at least identifiable regionally (Chen et al., 2020; Diamond & Lyons, 2018; Liu et al., 2020, A. Q. Liu et al., 2019; Planavsky et al., 2018; Shang et al., 2019; Sperling et al., 2014; Tang et al., 2020; Wang et al., 2018; Zhang et al., 2018; Zhang et al., 2016). Some paleoredox proxy data used for arguing an elevated p O 2 in the interval of 1.4–0.9 Ga, however, are apparently contradictory.…”
Section: Introductionmentioning
confidence: 97%